2023
DOI: 10.1097/med.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches to the adrenal gland

Abstract: Purpose of reviewReview the literature on the surgical management of adrenal diseases, highlighting the various surgical approaches and their respective pros and cons. Recent findingsMinimally invasive adrenalectomy is commonly used for small and benign adrenal tumors, whereas open adrenalectomy is preferred for larger tumors and primary adrenal malignancy. Although minimally invasive adrenalectomy results in shorter recovery and fewer complications compared with open, the latter offers better oncologic outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The management of adrenal myelolipomas largely depends on the size of the tumor and the presence of symptoms [ 7 ]. Small, asymptomatic lesions are often managed conservatively with follow-up imaging, typically using CT or magnetic resonance imaging, to monitor for any changes in size or symptoms [ 8 ]. While the optimal frequency of imaging remains undetermined, current suggestions propose a single follow-up scan at 3–6 months for radiologically suspicious lesions not initially removed, or within 12 months for seemingly benign masses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of adrenal myelolipomas largely depends on the size of the tumor and the presence of symptoms [ 7 ]. Small, asymptomatic lesions are often managed conservatively with follow-up imaging, typically using CT or magnetic resonance imaging, to monitor for any changes in size or symptoms [ 8 ]. While the optimal frequency of imaging remains undetermined, current suggestions propose a single follow-up scan at 3–6 months for radiologically suspicious lesions not initially removed, or within 12 months for seemingly benign masses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgical treatment of adrenal tumors including laparoscopic surgery and robotic surgery has become the standard surgical treatment for most small- to medium-sized adrenal tumors ( 25 ). Recent studies have indicated that the difficulty and risk of minimally invasive surgeries, such as posterior RLAS, are affected by factors including the complexity of the relationship between the tumor and the surrounding organs, the richness of the blood supply to the tumor, the distribution of blood vessels, and the endocrine function of the tumor itself ( 26 - 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decision regarding surgical intervention is individualized for those measuring 4-6 cm, considering factors such as the patient's overall health, symptoms, radiological characteristics, and the likelihood of malignancy (Jackson, 2023;Kahramangil et al, 2022). Techniques like laparoscopic or retroperitoneoscopic adrenalectomy are commonly employed, offering advantages like smaller incisions, reduced postoperative pain, shorter hospital stays, and faster recovery compared to traditional open surgery (Sada & McKenzie, 2023;Sancho et al, 2012). Therefore, this study aims to identify the prevalence of adrenal incidentaloma and subsequent clinical practice among 383 consecutive patients in Armed Forces Hospital.…”
Section: Key Considerations In Managing Aismentioning
confidence: 99%